The Influence of Dry Rendering and Ultrasonic?Assisted Extraction on DPPH Radical Scavenging Activity of Red Fruit (Pandanus conoideus) - Arifah, Mitsalina Fildzah; Kurniasih, Kholif Sholehah Indra; Kurniawati, Endah; Erlinaningrum, Mustika; Melanie, Zaskia Nora (MEDIA ILMU KESEHATAN, 2025)
Background: Red fruit (Pandanus conoideus) is a source of antioxidant compound components. Extraction methods can affect the antioxidant activity of the red fruit oil (RFO). Dry rendering is often used in conventional oil extraction, but it can potentially degrade antioxidant components. Currently, ultrasonic-assisted extraction (UAE) is a modern, yet underexplored method for oil extraction.Objective: This study aims to compare the extraction method on the antioxidant activity of RFO. Methods: The extraction methods included dry rendering and ultrasound-assisted extraction (UAE) using water and n-hexane as solvents. The flavonoid and phenolic contents, percentage yield, and DPPH free radical scavenging antioxidant activity were evaluated in RFO.Results: The results showed that the % yield with dry rendering was higher than in the UAE. The three extracts showed the presence of flavonoids and phenolics based on FeCl3 and AlCl3 tests. The highest antioxidant activity was in the dry rendering method (0,13% w/v) compared to UAE-water (0,98% w/v) and UAE-n hexane (1,47% w/v). Dry rendering could separate bioactive compounds with the highest % yield and inhibit DPPH free radicals with high temperatures, and without solvents. Conclusion: The dry rendering was selected as the extraction method, resulting in higher yields and antioxidant compounds in EBM compared to UAE.